Government Trust, Social Trust, and Citizens' Risk Concerns: Evidence from Crisis Management in China. Issue 2 (4th March 2019) - Ma, Liang; Christensen, Tom
Abstract: Citizens' trust in government and other people is crucial to their perceptions of social risks. In this study, we examine the effects of institutional and social trust on citizens' risk perceptions. Our analysis of a 2013 national survey conducted in 30 provincial capitals in China reveals that risk perceptions focus on two factors: public emergencies (e.g., traffic accidents) and public health threats (e.g., food safety). We found that only citizens' trust in central government was significantly negatively correlated with perceived emergencies, while trust in local government was marginally positively correlated with perceived emergencies. Social trust was not correlated with perceived emergencies, and none of the three trust variables was significantly correlated with perceived health threats. Our results revealed that the demographic variables gender, age, education, media exposure, and religious belief are all relevant for citizens' risk perceptions.